Effects of vitamin D supplementation on depressive symptoms in type 2 diabetes mellitus patients: Randomized placebo-controlled double-blind clinical trial. Issue 4 (July 2019) - Omidian, Mahsa; Mahmoudi, Maryam; Abshirini, Maryam; Eshraghian, Mohammad Reza; Javanbakht, Mohammad Hassan; Zarei, Mahnaz; Hasani, Hossein; Djalali, Mahmoud
Abstract: Aim: Diabetes increases the odds of depression and depression is often associated with poor glycemic control and complications of diabetes. Vitamin D is also believed to improve glycemic control and ameliorate depressive symptoms. Therefore, we examined effects of vitamin D monotherapy (without antidepressant drugs) on depressive symptoms in Type 2 diabetic patients with mild to moderate depressive symptoms. Methods: We conducted 12 weeks, placebo-controlled, double-blind, randomized trial on 68 subjects with T2DM and mild to moderate depressive symptoms. Subjects received 100 μg (4000 IU) vitamin D (n = 32) or placebo (n = 34) daily. Beck Depression Inventory-II (BDI–II–PERSIAN) was applied for assessment of the severity of depression. Depression scores and metabolic profiles were measured at the beginning and end of trail. Results: after 3 months of vitamin D supplementation, mean values of 25(OH) D increased from 15.5 ± 8.8 to 32.2 ± 8.9 ng/ml (p-value <0.001) in the vitamin D group. Moreover, BDI-II scores decreased from 15.2 ± 9.6 to 9.8 ± 7.2 (p-value <0.001) in the vitamin D group and 15.5 ± 11.2 to 13.7 ± 11.5 (p-value = 0.03) in placebo group. This decrease in BDI-II scores were significant (27.6% vs 10.8%) compared with placebo (p-value = 0.02). In term of metabolic profiles, mean change in level of Hemoglobin A1c (HbA1c), insulin and triglycerides (TG) were significantly higher in response to the treatment with vitamin D compared to placebo (p-value <0.02). Conclusions: In conclusion, supplementation of vitamin D in T2DM patients may protect these patients against the onset of major depressive disorder (MDD), with noticeable favorable effects on measures of metabolic profiles. Trial registration: NCT03008057